Study on the Trace Species in the Stratosphere and Their Impact on Climate - 陈月娟 周任君 施春华 毕云 (Advances in atmospheric sciences, 2006)
The trace gases （O3, HCl, CH4, H2O, NO, NO2） in the stratosphere play an important role, not only in the photochemical processes in which the ozone layer destroyed, but also in the radiative processes. In this paper, we review the works on the distribution and variation of the trace gases in the stratosphere and their impact on climate, which have been carried out at the University of Science and Technology of China in the recent 20 years. The Halogen Occultation Experiment （HALOE） data were used to analyse the distribution and variation of the mixing ratio of these trace gases and the temperature trends in the stratosphere in the most recent decade. And the reanalyzed National Centers of Environmental Prediction （NCEP）/NCAR data were also used to give the temperature trends and compared with the results from HALOE data. Numerical simulations were also carried out to study the impact of ozone depletion on the global climate. In this review, the distributions of the trace gases, especially those over the Qinghai-Xizang Plateau, are discussed, and the variations and trends for the trace gases in various levels in the stratosphere have been given for the most recent decade. The temperature variation and the cooling trend obtained from HALOE data in the middle and lower stratosphere for the last 13 years are significant, which agree well with the results from NCEP/NCAR data. While the temperature trend in the upper stratosphere in this period do not seem to have much cooling. The numerical simulations show that either the Antarctic ozone hole or the ozone valley over Qinghai-Xizang Plateau affect not only the temperature and circulation in the stratosphere, but also the temperature, pressure and wind fields in the troposphere, then lead to the global climate change.